The Kandings: A Study on Sex for Drugs in Iligan City - Along, Jovell Nicole; Labadisos, Renebel (Journal of Interdisciplinary Perspectives, 2024)
Drug addiction in the Philippines is still rampant and widely perceived to be the root of poverty, injustice, and powerlessness (Simbulan et al., 2019). This phenomenon gave rise to a multifaceted, overlapping problem. One of these issues is the practice of exchanging sex for drugs, which led to the emergence of Kandings. This study dwells on the case of Iligan City. Drawing concepts from the social exchange theory of George Homans and utilizing a qualitative case study, ten key informants were interviewed through snowball sampling, aged 16 and older. Findings shed light on the origins of the term Kanding as perceived by the informants, a term they believed had its roots primarily in the existence of illegal drug trading in Iligan City. Moreover, the informants represent a disadvantaged group with limited resources, which explains the reasons they manifest experiences as reflected in the typologies of Kanding, mainly the sex for drugs Kanding, the Kanding as an intimate partner, the Kanding as a sex worker, and the Kanding for self-gratification. Despite challenges, including stigma, unresolved transactions, and the acquisition of sexually transmitted infections, they engage in this behavior to obtain access to illegal drugs and earn money with drug users as their typical sexual partners. However, the informants maintained their optimism, wanting the best for their families, their children's success, and their strong faith in God to support them in overcoming these challenges.